PRINSIP KESANTUNAN BERBAHASA ANTARA PEMANDU WISATA DAN WISATAWAN JEPANG DI CANDI PRAMBANAN (KAJIAN ANALISIS PRAGMATIK) - Atiqah, Annisaa Nurul; Salindri, Yerika Ayu (Kepariwisataan: Jurnal Ilmiah, 2018)
The world of tourism is synonymous with services and services. One of service is tour guide. Tour guides are considered as the main actors in the world of tourism. Service actors interact directly with tourists to explain and provide assistance. Prambanan temple is the largest Hindu temple in Indonesia that holds much history. Therefore tour guide is the first source of information for foreign, especially Japanese. As a provision to communicate with Japanese tourists, need to understand the principle of language politeness in science pragmatic to support the success of communicating. This research uses descriptive qualitative method. Keywords: Tour guide, principles of politeness, pragmatics